Geographic Information Systems (GIS) Based Accessibility Modeling Approach in Micro Scale Considering Physically Disabled Users: Case Study of Mimar Muzaffer Campus, Selcuk University - Kıvanç Ertuğay (Iconarp International Journal of Architecture and Planning, 2018)
The concept of physical accessibility refers to the availability, capability, comfort, convenience of transportation processes considering different urban obstacles / barriers and costs.  In this context, there are many approaches for the measurement and evaluation of physical accessibility in the literature which are used extensively as a decision support especially in transportation, geography and city and regional planning related disciplines.